Answer:
a. FALSE
b. FALSE
c. FALSE
d. TRUE
Step-by-step explanation:
Statement a.
2 (3 - 4 y) = 6 - 4 y
use distributive property on the left:
6 - 8 y which is NOT 6 - 4 y then, FALSE statement
Statement b.
3 + 5 (9 + 2 n) = 48 + 5 n
apply distributive property on the left:
3 + 45 + 10 n = 48 + 10 n which is NOT 48 + 5 n then , FALSE statement
Statement c.
9 - 3 (y - 2) = 3 - 3 y
apply distributive property on the left:
9 - 3 y + 6 = 15 - 3 y which is NOT 3 - 3 y then, FALSE statement
Statement d.
3 (6 x - 2) - 7 = 18 x - 13
apply distributive property on the left:
18 x - 6 - 7 = 18 x - 13 which IS the same as 18 x - 13 then , TRUE statement